Socio and Demographic Determinants of Neonatal Mortality in Bangladesh (International Journal of Engineering and Computer Science, 2017)
Neonatal are not only the assets but also they are the future of a country or a nation. Women are core of development because they bear children and they are nearly half of the total population. Neonatal mortality is powerful indicators to measure overall health situation of a country. The aim of this study is to identify the important effects of socio-demographic characteristics on neonatal mortality. For this reason, the study uses the data extracted from the Bangladesh Demographic and Health Survey (BDHS) 2011. For this, a number of 8753 rural and urban women have been interviewed through a structured questionnaire by purposive sampling technique. In this study, Chi-square test, logistic regression has been employed to determine which factors that effect on neonatal mortality. In the analysis, it is indicated that mothers education and occupation, Fathers education and occupation ,wealth index, succeeding birth interval (in month) , birth order, toilet, diarrhea, mothers age and watches TV are significant effects on neonatal mortality.